CHANGE INITIATIVE: DOES TEACHER CERTIFICATION MATTERS? - Ema Dauyah; Putri Dini Meutia (Jurnal Dedikasi Pendidikan, 2020)
This paper attempts to discuss the change issue which is the implementation of teacher certification policy that has been implemented in Indonesia. Teacher certification in Indonesia has been implemented for almost a decade and there is not much significant evidence yet about the effect of teacher certification program on students' outcomes. This essay tries to look at the aspects that make the program successful and what are the challenges that might be faced by teachers. In exploring the issue this paper will use the following approach. Firstly, the notion of change will be discussed and then followed by the discussion of teacher certification. Then, framed against this inquiry will be the introduction of a case study based on the implementation of the teacher certification program in Indonesia.  Along with the case study, the difficulties of implementing this program will be presented. Finally, several thoughts and considerations of the best solution for teachers and policymakers to respond to the situation will be drawn accordingly.